Specialized regional National Guard brigades - the Army's federal disaster response force. - Emmons, Kristina A. (Fort Leavenworth, KS : U.S. Army Command and General Staff College, 2003)
The unthinkable occurred on September 11th and forced the United States to recognize the potential threats as well as the need to prepare more thoroughly for the potential consequences of such threats. The question still remains, who will provide military assistance to civil authorities in the event of a significant disaster? To answer the monograph question, this author presents a framework of Department of Homeland Security, Northern Command, and the potential missions of the Army under Civil Support, just one function of Homeland Security. The monograph then presents options for the Army by describing three response forces under NORTHCOM during a disaster. These options include using the disaster stricken state's NG units in federal status, using a non-specialized active Army unit, or using regionally located, specialized NG brigades.